Effect of flexible plates and micro-orifices on acoustic filter response for frequency-specific earplugs - Akira SANADA (The Japan Society of Mechanical Engineers, 2020)
In recent years, the use of earplugs with analog acoustic band pass filters has gained prominence. These earplugs can protect the ears of factory workers, who work in noisy environments, and simultaneously allow for necessary sounds such as colleagues' voices, danger alarms, and equipment-failure sounds to be heard. However, certain doubts still exist regarding the ability of these earplugs to protect the ears of the workers, particularly for low frequency ranges because of the relatively wide passing frequency ranges of sounds. From this standpoint, there exists a requirement for earplugs that can precisely control the passing amount and range of sounds in different working environments. Thus, we investigated an earplug with a simple lightweight structure, involving a filter consisting of a micro-orifice and flexible elastic plate. First, the frequency response of the proposed earplug was theoretically modeled using the transfer matrix method for each component. Second, the validity of the model was established experimentally, as confirmed by the results. Moreover, the proposed earplugs were confirmed to provide sufficient insulation against noise in a low frequency range and simultaneously allow for efficient passage of sounds in the range of 1–2 kHz. Further fine tuning can be expected by changing the detailed properties of the components.